Effect of back percussion along the meridian on lung function in patients with pulmonary dysfunction in recovery period of stroke (循经叩背对脑卒中恢复期合并肺功能障碍患者肺功能的影响) - PENG Yajie (彭雅洁) (中西医结合护理)
Objective To investigate the effect of back percussion along the meridian on lung function in patients with pulmonary dysfunction in recovery period of stroke. Methods Totally 90 patients with pulmonary dysfunction in recovery period of stroke were randomly divided into the observation group and control group, with 45 cases in each group. All patients received comprehensive rehabilitation therapy combined with routine care, and those in the observation group were given back percussion therapy along the meridian. The indexes of pulmonary function including partial pressure of oxygen (PaO2), partial pressure of carbon dioxide in artery (PaCO2) and oxyhemoglobin saturation (SaO2) were observed before and after treatment. The 6-minute walking distance, scores of Modified British Medical Research Council (mMRC), Short Form 36 Health Survey Questionnaire (SF-36) and satisfaction degree of two groups were compared. Results Patients in the observation group achieved better outcomes of PaO2、PaCO2、SaO2 compared with those in the control group (P＜0. 01). Patients in the observation group had a longer 6-minute walking distance and lower score of mMRC compared with those in the control group after intervention(P<0. 01). The scores of SF-36 and satisfaction assessment in the in the observation group were higher than those in the control group (P<0. 01). Conclusion The back percussion therapy along the meridian is potentially effective to improve the lung function of patients in recovery period of stroke, and improve the recovery of pulmonary function and quality of life. (目的 探讨循经叩背对脑卒中恢复期合并肺功能障碍患者肺功能的影响。方法 选取2019年2月—2021年2月科室收治的脑卒中恢复期合并肺功能障碍患者90例, 采用随机数字表法分为观察组与对照组, 各45例。对照组给予常规护理, 观察组在常规护理的基础上给予循经叩背。比较两组患者肺功能指标, 包括血氧分压(PaO2)、二氧化碳分压(PaCO2)和血氧饱和度(SaO2), 比较两组患者6 min步行距离(6MWD)、改良英国医学研究会呼吸困难指数(mMRC)评分、简明健康状况调查问卷(SF-36)评分与护理满意度。结果 干预后, 观察组PaO2、PaCO2、SaO2指标改善幅度优于对照组, 差异有统计学意义(P＜0. 01); 干预后, 观察组患者6MWD高于对照组(P<0. 01), mMRC评分低于对照组(P<0. 01); 观察组患者SF-36评分、护理满意度均高于对照组(P<0. 01)。结论 循经叩背能有效改善脑卒中患者肺功能, 对促进患者肺功能康复和提高患者生活质量具有积极意义。)